PENGARUH GOODWILL, ASET TAK BERWUJUD LAINNYA, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Farahiyah, Raudhatul; Muzahid, Mukhlisul; Herwinsyah, Reynold (Politeknik Negeri Lhokseumawe, 2025)
Abstract: This study aims to determine the effect of goodwill, other intangible assets, company size, and leverage on company value in companies listed on the Jakarta Islamic Index in 2020-2024. The data used are annual financial reports from 2020-2024. The research population consists of companies listed on the Jakarta Islamic Index in 2020-2024. Data sources were obtained from each company's published financial statements. The sampling technique used purposive sampling, and based on the sample selection criteria, 10 companies were selected for observation in this study. Data analysis was conducted using multiple linear regression with the assistance of Eviews version 12. The results of the study indicate that goodwill and company size have a significant negative effect on company value, while leverage has a significant positive effect on company value, and other intangible assets have no effect on company value. The R2 test results show that 35.21% of the independent variables explain the variation in company value.Keywords: Goodwill, Other intangible assets, Company size, Leverage, and Company value